The Challenges of Teaching Speaking to High School Students through Zoom Video Conference Application - A’isy, Qonita; Mufaridah, Fitrotul; Nurkamilah, Nurkamilah (Pubmedia Jurnal Pendidikan Bahasa Inggris, 2024)
Video conferencing is often used not only for webinar and other online meetings, but also for teaching and learning process. Some applications such as the Zoom Application are very helpful for students and teachers in the teaching and learning process. This research is about the obstacles faced, namely electronic media and internet quotas for online learning. Not all students are equal when it comes to economics. The problems of this research are how the teacher teaches speaking in online class and the challenges of teaching speaking through Zoom Video Conference Applications. The findings revealed that the English teachers provided relevant video as speaking model and engaged students to speaking practice in pair or small group to gain online learning experience. Meanwhile, teachers found several obstacles in online learning with the issues of students’ presence and motivation because of internet connectivity problems. the effectiveness of the learning process was affected. These findings contribute to highlighting the importance of addressing the digital divide in online speaking class to ensure equitable learning opportunities for all students.